-n-1=-6

Simple and best practice solution for -n-1=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -n-1=-6 equation:


Simplifying
-1n + -1 = -6

Reorder the terms:
-1 + -1n = -6

Solving
-1 + -1n = -6

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + -1n = -6 + 1

Combine like terms: -1 + 1 = 0
0 + -1n = -6 + 1
-1n = -6 + 1

Combine like terms: -6 + 1 = -5
-1n = -5

Divide each side by '-1'.
n = 5

Simplifying
n = 5

See similar equations:

| x+(x+2)+(x+3)+(x+4)=212 | | (5x^3+5x^2-4x-6)+(7x^3-2x^2-5x+1)= | | 5(g-7)=45 | | (x+4)x(x+4)=100 | | 3x+2=31 | | (3x-5)(5x-6)= | | 160=8(30-2d) | | 0.9(z+0.5)=-1.2(z+18) | | 2t=32 | | y=15x+250 | | 25.3=w-14.9 | | 3(b-2)=-3 | | 3(n+1)=-15 | | (y^7-y^3)-(y^4-y)= | | y-26=3 | | 40x+18x-3=468 | | x^2-6x+y+5=0 | | 3t+17-4t=-18 | | 2v-1=1 | | -1-2x(1-7)=8 | | -36.8+9.2x= | | 18x+40(x-3)=468 | | 3x(x+10)=99 | | 9=n/13 | | (4x-11)-(-16x-17)= | | 4x^2+25y^2-100y=0 | | 3*(-1)+2*2-3x=-2 | | 3(t-4)=-2(t-3)+14 | | (X-4)(x+12)= | | 2x-21=x+4 | | x^2+17=19 | | 40x-18(x-3)=468 |

Equations solver categories